The Construction of Sufism in Novel Arinillah by Taufiq Al-Hakim and its Urgence for Modern Muslims - Safitri, Eka (Institute of Research and Public Service Universitas Jenderal Soedirman, 2023)
This research is library research that aims to examine and analyze the values of Sufism in the novel Arinillah by Taufiq Al-Hakim. Sufism values are listed in each storyline, and the depiction of the characters facing life's problems in the novel Arinillah by Taufiq Al-Hakim. This research is a qualitative descriptive study with stages, namely the stages of providing data, analyzing data, and presenting the results of data analysis. The data source in this research is Novel Arinillah Karya Taufiq Al-Hakim. The data collection technique used reading and note-taking techniques, and the data were analyzed using qualitative descriptive methods. As for the results of this study, Taufiq Al-Hakim gave the values of the spirituality of Sufism in the novel Arinillah. The Sufism values contained in the novel are patience, tawakkal, zuhud, pleasure, repentance, divine love, and faqir. These values can be integrated into modern Muslim life to solve spiritual thirst. The individualistic, materialist, hedonistic style of community life that emphasizes ratio can be reduced by integrating the values of zuhud, tawakkal, and patience. The application of value of Sufism is very important to be applied during increasingly modern life and increasingly sophisticated technological developments.